Surface production operations /Maurice Stewart. Vol. 3, Facility piping and pipeline systems - Stewart, Maurice
The third volume presents readers with a "hands-on" manual for applying mechanical and physical principles to all phases of facility piping and pipeline system design, construction, and operation. Packed with charts, tables, and diagrams, this authoritative book provides practicing engineer and senior field personnel with a quick but rigorous exposition of piping and pipeline theory, fundamentals, and application.